HAWKING RADIATION AND PARTICLE EMISSIONS ON KERR - NEWMAN - VAIDYA BLACK HOLES - Hasbi Salimi, Ahmad
In this research, the analysis of Hawking radiation on a nonstationary Kerr – Newman – Vaidya black hole was analyzed using semiclassical approaches. The nonstationary term ???? in the black hole is equivalent to a mass change with respects to time and radial coordinates. The Hawking temperatures were derived using three methods: Two semiclassical methods, including the radial null geodesic method and the complex path analysis, and the Bekenstein – Hawking temperature formulation. These three methods gave the same temperature. In general, the Hawking temperature obtained was inversely proportional to the mass and nonstationary term. In order for the temperatures not to be imaginary values, the black holes must satisfy (????+????)2?????2+????2 condition, with ???? is the mass, ???? is the angular momentum and ???? is the electric charge of the black holes. The entropy of black holes was derived using the Bekenstein – Hawking formulation in ???????????? form and the black hole dynamics equation in the form of ????????????????/????????. The two types of particle emission as Hawking radiation were analyzed: particle emission using the Klein-Gordon equation and Dirac particle emission using the Dirac equation. The wave functions of these two particle emissions are then analyzed using the WKB approximation to calculate the effect of particle emission on the Hawking temperature of the black hole. The main difference between the emission results of scalar particles and Dirac particles is that there is a characterization term consisting of E the energy of the Dirac particle, j the angular momentum of the Dirac particle and e the electric charge of the Dirac particle. In order for the temperature to remain positive, the particle and the black hole must satisfy ????(????+????)?????????+????????.